Light-Controlled Polarization of MM-Waves with Photo-Excited Gratings in a Resonant Semiconductor Slab - Yurchenko, V.; Navruz, T.; Ciydem, M.; Altintas, A. (Advanced Electromagnetics, 2019)
We investigated photoconductive gratings in the resonant semiconductor layers as light-controlled polarizers for the millimeter (MM) waves. We compared the effects of strip-like, wire-like, and fin-like gratings excited by the red light and the IR radiation in Silicon wafers, respectively. The fin-like gratings are shown to be the preferred structures that can operate at the limited light intensity. The light-sensitive shift of maxima of transmitted power and polarizing efficiency towards the lower frequency band is observed. The effect makes photoconductive gratings and similar patterns potentially suitable for the design of light-controlled frequency-tuning and frequency-modulating components of resonant quasi-optical devices.